Pengaruh Tingkat Orang Tua Terhadap Perkembangan Sosial Emosional Anak Usia 4-5 Tahun - Azhar Febrianti; Aini Loita; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The social-emotional development of early childhood is a crucial aspect that influences children’s ability to recognize and manage emotions, as well as to establish healthy social relationships. This study aims to analyze the influence of parental education level on the social-emotional development of children aged 4-5 years in Babakan Asih Subdistrict, Bojongloa Kaler District, Bandung City. The study employed a quantitative correlational approach using a survey method. The sample consisted of 50 parents with early-aged children, selected through purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using Pearson correlation with the aid of statistical software. The findings indicate a positive and significant relationship between parental education level and children’s social-emotional development, with a correlation coefficient of 0.549 and a significance level of 0.000. These results suggest that the higher the parental education level, the better the social-emotional development of the child. The study recommends increasing parenting literacy among parents, both through formal and non-formal education, to support the holistic development of children. Support from early childhood education institutions and local government is also necessary to provide capacity-building programs for parents in developmentally appropriate parenting